A Note on the Binding Energy for Bosons in the Mean-Field Limit - Boßmann, Lea; Leopold, Nikolai; Mitrouskas, David; Petrat, Sören (Journal of Statistical Physics, 2024)
We consider a gas of N weakly interacting bosons in the ground state. Such gases exhibit Bose–Einstein condensation. The binding energy is defined as the energy it takes to remove one particle from the gas. In this article, we prove an asymptotic expansion for the binding energy, and compute the first orders explicitly for the homogeneous gas. Our result addresses in particular a conjecture by Nam (Lett Math Phys 108(1):141–159, 2018), and provides an asymptotic expansion of the ionization energy of bosonic atoms.
CRIS-Team Scopus Importer:2024-10-02
Keywords: Asymptotic expansion; Binding energy; Bose gas; Bose–Einstein condensation; Mean-field limit